1α, 25(OH)2D3 reverses exhaustion and enhances antitumor immunity of human cytotoxic T cells. Issue 3 (22nd March 2022) - Li, Peng; Zhu, Xinhai; Cao, Guangchao; Wu, Ruan; Li, Ke; Yuan, Wenhui; Chen, Biyun; Sun, Guodong; Xia, Xichun; Zhang, Hua; Wang, Xiao; Yin, Zhinan; et al.
Abstract : Background: Epidemiological surveys have revealed that low serum vitamin D level was correlated with increased risk of tumors. Dysfunctional T cells in patients with tumor are characterized as exhausted with high levels of immune checkpoint receptors (ICRs). However, whether the reduced level of vitamin D in patients with cancer correlates with cytotoxic T-cell exhaustion is unknown. Methods: Periphery blood samples from 172 patients with non-small cell lung cancer (NSCLC) were prospectively collected. Patients with NSCLC received one course of intravenous docetaxel (75 mg/m 2 ) followed by treatment with or without rocaltrol at a dose of 0.5–2.0 µg/day for total of 3 weeks. We performed phenotypical and functional analysis of T-cell through flow cytometry. Vitamin D receptor (VDR) knockout and overexpression CD8 + and Vδ2 + T cells were constructed using Cas9-gRNA targeted and overexpressing approaches to identify 1α, 25(OH)2 D3 /VDR-mediated transcription regulation for ICRs or antitumor activity in T cells. Results: We show that serum level of vitamin D is negatively correlated with expression of programmed cell death-1 (PD-1), T-cell immunoreceptor with Ig and ITIM domains (TIGIT), and T-cell immunoglobulin and mucin-domain containing-3 (Tim-3), but positively correlated with CD28 expression on CD8 + and Vγ9Vδ2 + T cells in patients with NSCLC. 1α, 25(OH)2 D3, the active form of vitamin D, promotes the nuclear translocation of VDR, which binds to the promoter region of Pdcd1, Tim3, and Tigit genes and inhibits their expression. Besides, 1α, 25(OH)2 D3 pretreatment also promotes the methylation of CpG island in the promoter region of the Pdcd1 gene and increases H3K27 acetylation at the promoter region of the Cd28 gene, which leads to surface PD-1 downregulation and CD28 upregulation, respectively. We further reveal that VDR-mediated Ca 2+ influx enhanced expression of Th1 cytokines via T-cell receptor activation. Functionally, 1α, 25(OH)2 D3 pretreated CD8 + T cells or Vγ9Vδ2 + T cells showed increased Th1 cytokine production and enhanced antitumor immunity. Finally, oral 1α, 25(OH)2 D3 could also decrease expression of PD-1, Tim-3, TIGIT and increase expression of CD28, resulting in cytokine production (associated with antitumor immunity) by cytotoxic T cells of patients with NSCLC. Conclusions: Our findings uncover the pleiotropic effects of 1α, 25(OH)2 D3 in rescuing the exhausted phenotype of human cytotoxic T cells in patients with tumor and in promoting their antitumor immunity. Trial registration number: ChiCTR2100051135.